Silene nemrutensis (Caryophyllaceae), a new species from south-eastern Anatolia - Yildiz, Kemal; Çirpici Ali̇; Dadandi, Mehmet Yaşar; Firat, Mehmet (Phytotaxa, 2017)
A new perennial species, Silene nemrutensis (Silene sect. Spergulifoliae, Caryophyllaceae), is described and illustrated from SE-Anatolia. A macromorphological comparison with the similar species S. arguta is given as well as the ultrastructure of the seeds and pollen grains. Original photographs, geographical distribution, habitat and IUCN conservation status are also provided.